2022
DOI: 10.1002/jcsm.13133
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of questionnaires for eating‐related distress among advanced cancer patients and families

Abstract: Background Eating-related distress (ERD) is one type of psychosocial distress among advanced cancer patients and family caregivers. Its alleviation is a key issue in palliative care; however, there is no validated tool for measuring ERD. Methods The purpose of this study was to validate tools for evaluating ERD among patients and family caregivers. The study consisted of a development and validation/retest phase. In the development phase, we made preliminary questionnaires for patients and family caregivers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For example, Altman and others conducted a qualitative study of patients with small-cell lung cancer with the goal of developing a conceptual model to capture symptoms associated with this malignancy. Although these investigators described a variety of symptoms, a germane quotation from a patient – ‘I don’t eat anywhere near like I ate before’ – captures the fact that anorexia is a noteworthy symptom in many patients with cancer and requires clinical attention 1 . Similarly, Amano and others developed and validated a questionnaire for eating distress in patients with advanced cancer 2 .…”
Section: Characterization Of Anorexia In Patients With Cancermentioning
confidence: 99%
“…For example, Altman and others conducted a qualitative study of patients with small-cell lung cancer with the goal of developing a conceptual model to capture symptoms associated with this malignancy. Although these investigators described a variety of symptoms, a germane quotation from a patient – ‘I don’t eat anywhere near like I ate before’ – captures the fact that anorexia is a noteworthy symptom in many patients with cancer and requires clinical attention 1 . Similarly, Amano and others developed and validated a questionnaire for eating distress in patients with advanced cancer 2 .…”
Section: Characterization Of Anorexia In Patients With Cancermentioning
confidence: 99%
“…Furthermore, there had been no questionnaire to measure the cancer cachexia-related QOL and eating-related distress in family caregivers. Therefore, tools that specifically measure eating-related distress experienced by patients with advanced cancer and their family caregivers were recently developed, respectively, 29 because eating-related distress, which can adversely affect QOL, is an important matter to address in holistic multimodal care for patients and family caregivers affected by cancer cachexia. For example, the PiCNIC study found that family-centered nutritional interventions that included advice for people with advanced cancer on improving the nutritional intake (energy and protein) had good potential to have positive effects on patients' nutritional status and eating-related distress.…”
Section: Holistic Multimodal Care For Cancer Cachexiamentioning
confidence: 99%